(untitled) (Ustozlar uchun, 2026)
International organizations play a crucial role in promoting cooperation, peace, economic development, and social progress among nations. They provide platforms for countries to address global challenges, including poverty, climate change, health crises, and international conflicts. Through coordinated efforts, these organizations contribute to sustainable development and strengthen diplomatic relations worldwide. This article explores the functions, significance, and impact of international organizations in contemporary society and examines their contribution to global stability and development.